Correlating Student Knowledge and Confidence Using a Graded Knowledge Survey to Assess Student Learning in a General Microbiology Classroom - Lacey Favazzo (American Society for Microbiology, 2014)
Knowledge surveys are a type of confidence survey in which students rate their confidence in their ability to answer questions rather than answering the questions. These surveys have been discussed as a tool to evaluate student in-class or curriculum-wide learning. However, disagreement exists as to whether confidence is actually an accurate measure of knowledge. With the concomitant goals of assessing content-based learning objectives and addressing this disagreement, we present herein a pretest/posttest knowledge survey study that demonstrates a significant difference correctness on graded test questions at different levels of reported confidence in a multi-semester timeframe. Questions were organized into Bloom’s taxonomy, allowing for the data collected to further provide statistical analyses on strengths and deficits in various levels of Bloom’s reasoning with regard to mean correctness. Collectively, students showed increasing confidence and correctness in all levels of thought but struggled with synthesis-level questions. However, when students were only asked to rate confidence and not answer the accompanying test questions, they reported significantly higher confidence than the control group which was asked to do both. This indicates that when students do not attempt to answer questions, they have significantly greater confidence in their ability to answer those questions. Additionally, when students rate only confidence without answering the question, resolution across Bloom’s levels of reasoning is lost. Based upon our findings, knowledge surveys can be an effective tool for assessment of both breadth and depth of knowledge, but may require students to answer questions in addition to rating confidence to provide the most accurate data.